LINGUISTIC CONSCIOUSNESS AND HISTORICITY. GHEVOND ALISHAN՚S COMPOSITION “UNDER THE FIR TREE: REFLECTIONS IN THE BOSOM OF DESERTED NATURE” - Hambardzumyan, Naira (Armenian Folia Anglistika, 2022)
The present article aims at studying the problems of historicity, linguistic consciousness, and philosophy of life as a constantly transforming chain that includes and circulates geopolitical and cultural processes. The primary aim of the study is to observe the author – world relations in the domain of language, consciousness and historicity, through which the essential inner features of the author’s meditations and philosophical thoughts are revealed, and historicity becomes a tool for regulating experience. Linguistic consciousness presupposes an open image of the world, in which geopolitical events, actions, and situations are summarized. Historicity, as a process of restoring information flows, is full of events and ensures the time and vitality of the geopolitical processes. At the same time, as a regulating depository of language+consciousness, it provides the ability of identifying the attitude towards most important historical events in Alishan’s experience. I have applied the phenomenological and historical-comparative methods focusing on semantic-typological procedures, the methodology of understanding. Father Ghevond Alishan’s composition “Under the Fir Tree: Reflections in The Bosom of Deserted Nature” which is a unique combination of world historiography, Christianity, and historical-philosophical thought, has so far not received all the attention it deserves.